Influence of the placement period on the development of professional identity for social education students - Susana María Garcia Vargas; Raúl González Fernández; Ana María Martín-Cuadrado (Sociedad Iberoamericana de Pedagogía Social, 2016)
The Social Education Degree placement for the National University for Distance Education (UNED) allows students to experience and reflect upon the labour situation. Its influence on the development of the student professional identity is an important subject for both placement tutors and teachers. The study combines the search for and analysis of qualitative and quantitative data to assess the influence of the Professional Placement III course, the students' first contact with the real business world, on the development of their professional identity. Throughout the research it has been possible to determine an emerging concept in the professional identity of students before the start of the placement, which changes and consolidates depending on their experience within the placement programme; these results are similar to those obtained in research relating to other professions similar to Social Education (Pontes, Ariza & Del Rey, 2010). Therefore, it can be stated that this course is an important variable that especially influences the development of the professional identities of future social educators.